Eksplorasi minat tren thrifting di kalangan generasi z: Analisis teori tindakan sosial max weber - iva, iva latifa (Maliki Interdisciplinary Journal, 2025)
This study aims to explore the interest in thrifting trends among Generation Z using Max Weber’s social action theory approach. The phenomenon of thrifting, which is buying second-hand clothes, is increasingly popular among university students as a form of alternative consumption that is not only economical, but also reflects awareness of environmental sustainability, self-expression, and social influence. This research uses a qualitative method with a grounded theory approach and involves eight students of UIN Malang as the main informants. The results showed that students’ motivation in thrifting is divided into four categories of Weber’s social action, namely rational action (price and quality considerations), value-oriented action (ecological awareness), affective action (emotional and aesthetic impulses), and traditional action (influence of social habits). The findings confirm that thrifting is a complex and multidimensional social activity, and reflects the lifestyle of young people who are adaptive to social and environmental issues.